IMD205: Multimedia for Information Presentation / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course discusses the theories and application of multimedia related to information presentation. It explores the techniques and skills in developing and producing interactive multimedia application using multimedia authoring tools.